2010
DOI: 10.1080/11250000902932841
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme activities and markers of oxidative stress in the life cycle of earthworm,Eudrilus eugeniae

Abstract: The main aim of this work is to provide basic data on the aspects of pro-oxidant and antioxidant processes in different life stages of Eudrilus eugeniae. The levels of antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT), along with the byproducts of lipid and protein oxidation, malondialdehyde (MDA) and protein carbonyl (PC), content were determined in the whole body of juvenile, sub-adult and adult earthworms. The SOD activity significantly (P < 0.05) decreased during development from juvenile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Studies using earthworms had shown toxic effects of BDE 29 , 30 in soil and thus an increased health risk (WHO 2004) subsequently. 31 The oxidative stress and reduction in thiol components were reported in Eudriluseugeniae 32 stressing the significance of impact of oxidant/antioxidant imbalance. The oxidant burden and the antioxidant depletion observed in the current study were well manifested in the symptoms such as rigidity, coiling, ataxia, constriction in the worms ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using earthworms had shown toxic effects of BDE 29 , 30 in soil and thus an increased health risk (WHO 2004) subsequently. 31 The oxidative stress and reduction in thiol components were reported in Eudriluseugeniae 32 stressing the significance of impact of oxidant/antioxidant imbalance. The oxidant burden and the antioxidant depletion observed in the current study were well manifested in the symptoms such as rigidity, coiling, ataxia, constriction in the worms ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were sacri ced immediately after exposure for 14 d to the four doses of the pesticides. Tissues were processed for biochemical study following the methods of Avi Kiran and Aruna [20] Enzymes assays were determined following the methods below…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…To initiate the reaction, H 2 O 2 was added to the mixture. The decrease in absorbance was taken at 470 nm (Ravi Kiran & Aruna, 2010).…”
Section: Analysis Of Antioxidant Enzymesmentioning
confidence: 99%